Saving the Fetus in Material Schizophrenia: The Role and Safety of Electroconvulsive Therapy (Ect) in Pregnancy - Abdul Karim, Othman; Syaratul Emma, Hashim; Anisah, Jalaluddin; Noraslawati, Razak (2018)
Managing schizophrenia during pregnancy often presents a clinical dilemma. Although pharmacological interventions are mostly effective for these disorders during pregnancy, there are few drawbacks for this approach. The potential teratogenicity and long duration of interventions required to control the symptoms somehow limits its usage during pregnancy. Here we described a case report of treatment-resistant schizophrenia successfully treated with ECT without obvious complication to the mother and her baby. Conclusion: Electroconvulsive therapy is an ideal alternative treatment for a patient with schizophrenia during pregnancy. ECT also will eliminate the potential side effects of antipsychotic medications on the mother and teratogenicity effect to the fetus, especially during the first trimester.